A PEMBERDAYAAN KELOMPOK WANITA TANI (KWT) AYU TANI PEKON BULUKARTO KABUPATEN PRINGSEWU MELALUI DIVERSIFIKASI OLAHAN BERBASIS BAYAM DAN JAHE - Ambar Wati, Desti; Elva Junita, Dera (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Aisyah Pringsewu, 2023)
The development of various preparations from spinach and ginger well includes efforts to support government programs through food diversification. The target of this activity is Kelompok Wanita Tani (KWT) Ayu Tani. The problem that occurs with partners is the limited ideas for processing spinach and ginger cultivation products. The solution offered to partners is to diversify processed spinach and ginger into Kembang Goyang and instant ginger drinks. This product was chosen to develop traditional food and drinks and has gone through a trial process and nutritional content analysis using a nutrisurvey application. The media used as a presentation tool is a product development recipe book. Apart from increasing knowledge and skills regarding food diversification, the team also provides education regarding packaging and product marketing techniques on social media as whatsapp, instagram, and facebook. Keywords: Food Diversification; Spinach; Ginger; Nutrition Products